Intervensi Pangan Fungsional Berbasis Kearifan Lokal dalam Upaya Preventif Stunting di Posyandu Teratai Bandar Lampung - Indah Oktaviani; Okta Yulia Sari; Fajar Islam Sitanggang; Muhammad Asril (Pakis Journal Institute, 2026)
Stunting is a chronic nutritional problem that hinders the physical and cognitive growth of toddlers. Despite the abundant potential of local food sources in Bandar Lampung City, their utilization as functional foods for stunting prevention remains suboptimal. This Community Service (PkM) activity aims to enhance the knowledge and skills of mothers with toddlers at Posyandu Teratai, Sukarame, through nutritional education and the introduction of local plant-based functional foods. The methods employed included counseling and person-to-person consultations, as well as the demonstration of applicable Supplementary Feeding (PMT) using local ingredients (sweet potatoes, bananas, eggs, and yogurt). Evaluation was conducted using pre-test and post-test instruments. The results showed a significant increase in the understanding of the definition of stunting (from 70% to 95%) and awareness of the advantages of local food (from 80% to 100%). Although sampling bias occurred in several indicators due to a significant increase in the number of participants during the intervention, overall, the personal consultation method was effective in clarifying the mothers' concerns. This program successfully instilled an understanding of the importance of processing local food as a fundamental step toward sustainable changes in family nutritional behavior.